Re-Remembering the Holocaust: A Look into "Judeo-Christian" Holocaust Denial (Relegere: Studies in Religion and Reception, 2012)
This paper explores the hermeneutical and theoretical problems associated with the term "Judeo-Christian" in an American political context. In particular, it focuses on how certain conservative Protestant groups surreptitiously espouse a political-theological agenda to replace their historical role of oppressor with that of victim. It examines a process I term "re-remembering" to demonstrate how this political-theological agenda necessitates a form of Holocaust denial.